Human repair‐related Schwann cells adopt functions of antigen‐presenting cells in vitro. Issue 12 (17th August 2022) - Berner, Jakob; Weiss, Tamara; Sorger, Helena; Rifatbegovic, Fikret; Kauer, Max; Windhager, Reinhard; Dohnal, Alexander; Ambros, Peter F.; Ambros, Inge M.; Boztug, Kaan; Steinberger, Peter; Taschner‐Mandl, Sabine
Abstract: The plastic potential of Schwann cells (SCs) is increasingly recognized to play a role after nerve injury and in diseases of the peripheral nervous system. Reports on the interaction between immune cells and SCs indicate their involvement in inflammatory processes. However, the immunocompetence of human SCs has been primarily deduced from neuropathies, but whether after nerve injury SCs directly regulate an adaptive immune response is unknown. Here, we performed comprehensive analysis of immunomodulatory capacities of human repair‐related SCs (hrSCs), which recapitulate SC response to nerve injury in vitro. We used our well‐established culture model of primary hrSCs from human peripheral nerves and analyzed the transcriptome, secretome, and cell surface proteins for pathways and markers relevant in innate and adaptive immunity, performed phagocytosis assays, and monitored T‐cell subset activation in allogeneic co‐cultures. Our findings show that hrSCs are phagocytic, which is in line with high MHCII expression. Furthermore, hrSCs express co‐regulatory proteins, such as CD40, CD80, B7H3, CD58, CD86, and HVEM, release a plethora of chemoattractants, matrix remodeling proteins and pro‐ as well as anti‐inflammatory cytokines, and upregulate the T‐cell inhibiting PD‐L1 molecule upon pro‐inflammatory stimulation with IFNγ. In contrast to monocytes, hrSC alone are not sufficient to trigger allogenic CD4 + and CD8 + T‐cells, but limit number and activation status of exogenously activated T‐cells. This study demonstrates that hrSCs possess features and functions typical for professional antigen‐presenting cells in vitro, and suggest a new role of these cells as negative regulators of T‐cell immunity during nerve regeneration. Main Points: Human repair‐related Schwann cells (hrSC) function as professional antigen‐presenting cells. HrSCs up‐regulate PD‐L1 upon pro‐inflammatory IFNγ stimulation. HrSCs hamper CD 4+ and CD 8+ T‐cell activation.